Methods of Measurement System Quality Assessment in Case of Two Devices - Krzysztof Kowal,; Michał Szymczak, (Journal of Basic & Applied Sciences, 2014)
The article discussed the selected methods of measurement systems analysis (MSA) in case of different devices usage. Analysis of variance is a common method, widely accepted and applied in industry to analyze measurement systems by taking into consideration different sources of variability: equipment, operators, parts and their interaction. Regression is a method which could simplify the analysis by shortening its time and decreasing sample size. It also may enable more clear and suitable answer. The included case study concerning two coordinate measuring machines (CMM) indicates the usefulness of the regression as a method for high precision and automated measurement systems comparison. Some actions resulting from the inferences can be undertaken by managers and engineers in industrial enterprises to reduce the cost of double measurements.